FLAR Collect: An ODK (Open Data Kit)-based free application to collect data on agronomic management and production costs of rice crops through mobile devices - CGIAR Research Program on Rice (2021)
This tool is freely available for users through Play Store: Search as ODK Collect2 https://play.google.com/ store/apps/details?id=org.odk.collect.android